Criminal Liability for Electronic Document Forgery: A Case Study of PT. Toyobo Japan - Sophia Lequin Theovani Purba; Thomas Poltak Sianturi; Theodora Verina Josephine Rouli Situmorang; Rosmalinda; Annisa Hafizhah (Journal of Law Perspectives Review, 2026)
This study aims to explain the legal regulation of electronic document forgery in Indonesia as well as the form of criminal liability in the case of electronic document forgery of PT Toyobo Japan. Forgery of electronic documents is regulated through the general provisions of the Criminal Code and special provisions in the Electronic Information and Transactions Law that provide a legal basis for the act of creating, altering, and distributing counterfeit digital documents. This study uses a normative juridical method with a legislative approach and a case approach, based on the analysis of primary and secondary legal materials. The results of the study showed that the perpetrators deliberately created fake email accounts and manipulated payment instruction documents to illegally divert funds. These acts meet the elements of intentionality, responsible ability, unauthorized access, and the creation of false electronic documents as stipulated in the Criminal Code and the ITE Law. Thus, the perpetrators can be held criminally responsible as the main perpetrator or participate based on the applicable legal provisions.